(untitled) (Research, Society and Development, 2021)
Society is moving towards new ideas related to the consumption of existing natural resources. For this reason, sustainability has gained a lot of space in everyday life in society. Through sustainable construction the environmental impact will be drastically diminished. Therefore, this article demonstrates a proposal for sustainable construction. Civil engineering has produced environmental impacts that can be minimized and determined. Therefore, it is necessary to seek a pleasant relationship with the environment, because the environment needs to be balanced, in order to be beneficial to the development of today’s society without consuming natural resources. The use of sustainable materials and the application of sustainable principles in construction have proven to be alternatives for sustainable development in the area of civil construction. This work aims to analyze a project executed of a children’s home with application of sustainable construction in civil engineering, which resulted in several national and international awards.